KASSIAN CHEPHAS (1845-1912): Dari Kolektivitas Menuju Subjektivitas - Farhan Adityasasmara (Pascasarjana Universitas Hindu Indonesia, 2017)
In general, this paper aims at making inventory of the response to the modernity that swept our nation lately. Camera and photography were chosen because it is a physical product of modernity. While the first photographer Kassian Chephas was chosen because he lives in the two worlds, namely Javanese and modernity. The conclusions generated in this study are (1) the world of photography shows the existence of psychological and historical gap between (art) photography and fine arts in Indonesia; (2) there is a change of orientation in view of self, namely: from the drowning silently in the flow of collectivity into an autonomous subject in the midst of modernity flow.